Noonan syndrome caused by RIT1 gene mutation: A case report and literature review - Zha, Ping; Kong, Ying; Wang, Lili; Wang, Yujuan; Qing, Qing; Dai, Liying (Frontiers in Pediatrics, 2022)
Objective: Noonan syndrome (NS), an autosomal dominant disease known as a RASopathy, is caused by germline mutations in mitogen-activated protein kinase pathway genes. A RIT1 gene mutation has been found to cause NS. The present study summarizes RIT1 gene mutation sites and associated clinical phenotypes. Methods: We retrospectively analyzed the clinical characteristics of a case of NS caused by RIT1 mutation in our hospital, and searched the PubMed database, China National Knowledge Infrastructure (CNKI) database and Wanfang database with the keywords Noonan syndrome and RIT1. Studies published between May 1, 2014 and July 1, 2021 were retrieved. Results: A total of 41 cases were analyzed, including 13 boys and 28 girls. There were 14 premature cases. The age at diagnosis was 4 days to 18 years, and 10 cases were diagnosed at 0–1 years of age. Common amino acid substitution positions included 57 (13/41), 95 (7/41), 82 (8/41) and 90 (4/41). A total of 63.63% cases had abnormal prenatal examination results, manifesting mainly as fetal neck edema, polyhydramnios and cardiac malformation. With respect to abnormal conditions after birth, 70%–80% of patients had typical developmental malformations of the face, neck and thorax; 19/35 patients had abnormal lymphatic development; and a portion of patients had short stature and motor development disorders. A total of 87.80% (36/41) patients had cardiac dysplasia, among which hypertrophic cardiomyopathy (HCM) accounted for 58.53%. A total of 84.62% of patients carrying the p.A57G mutation had HCM, but no HCM was found in patients with the p.G95A mutation. A total of 34.15% of patients had pulmonary artery or pulmonary valve stenosis (PVS). In patients with the p.M90I mutation, 75% had PVS. Patients with concurrent HCM and PVS accounted for 19.51%, and 48.78% of patients had supraventricular tachycardia. Conclusion: A RIT1 gene mutation causing NS was associated with a high rate of abnormal prenatal examination findings. Most patients had typical NS craniofacial deformities, and some have short stature and motor development disorders. The cardiac deformity rate was high, and HCM was common. Some patients had supraventricular arrhythmias. Heart abnormalities showed high heterogeneity, given the various mutation loci.